COVID-19 infection during pregnancy on perinatal and neonatal outcomes: a scoping review - Fauziah, Saidatul; Hasanbasri, Mubasysyir; Oktaria, Vicka (BKM Public Health and Community Medicine, 2023)
Purpose: COVID-19 infection has rapidly spread and caused a global pandemic, as stated by the World Health Organization on March 10, 2020. The incidence of COVID-19 tends to increase worldwide, including Indonesia, occasionally. With 6,422,529 confirmed cases, including 158,014 as of September 25, 2022, Indonesia has surpassed India and Bangladesh to become the nation with the third-highest confirmed cases in Asia. Although there have been reports of several cases of vertical transmission, the transmission of COVID-19 from mother to fetus was initially considered uncertain. Case reports of newborns (within the first 12 hours) with COVID-19 infection prove the possibility of intrauterine or extrauterine mother-infant vertical transmission. This study aimed to determine the effect of COVID-19 infection during pregnancy on perinatal and neonatal outcomes. Methods: This study employed the scoping review method, searching articles across several databases, including PubMed, Scopus, and Google Scholar, and adhered to the guidelines of PRISMA-ScR. Search for articles using the main keywords” pregnant women” or “pregnant” and “coronavirus” (or COVID-19 or 2019NCOV or SARS-CoV-2) AND (” perinatal outcome” or “neonatal outcome” or “pregnancy outcome”) published in 2019–2022. Results: The articles obtained were related to symptoms of COVID-19-positive pregnant women, perinatal and neonatal outcomes of COVID-19 pregnant women, and the identification of COVID-19 occurrence during pregnancy. Conclusion: A total of 22 articles reviewed found that pregnant women with COVID-19 symptoms experience adverse outcomes in perinatal and neonatal compared to those not infected with COVID-19. Pregnant women with COVID-19 infection show a higher risk of perinatal and neonatal outcomes such as premature, LBW, and NICU admission.